Short-term effects of thinning intensity on scenic beauty values of different stands - Deng, Songqiu; Yan, Jiafeng; Guan, Qingwei; Katoh, Masato (Journal of forest research, 2013)
Forest management has significant influences on the preferences of people for forest landscapes. This study attempted to evaluate the effects of thinning on the scenic value of forests. Five typical stands in Nanjing Wuxiangsi National Forest Park were subject to a designed thinning experiment from February to May 2007 with four intensities: unthinned, light-thinning, middle-thinning, and high-thinning. Next, people’s preferences for landscape photographs taken in plots with different thinning intensities were assessed by a scenic beauty estimation (SBE) developed by using normal function theory (N-SBE) 2 years after thinning. In order to resolve shortcomings of N-SBE, another SBE calculation method based on weighted sum theory (W-SBE) was developed in the study, and it was demonstrated to have the same reliability as N-SBE by statistical methods. Then, the difference of W-SBE between different thinning intensities was analyzed by paired samples T test. The results suggested that it was significant, at the 0.01 level, between unthinned plots and all thinned plots, and significant, at the 0.05 level, between high-thinning and light-thinning, and between high-thinning and middle-thinning, while there was no significant difference between middle-thinning and light-thinning. Finally, a stepwise regression model was established between W-SBE as the dependent variable and some possible impact preference factors as independent variables. This indicated that landscape value was diminished with increase of tree density, canopy density, and opening of understory, while the value improved with the increment of average diameter at breast height and tree height, species diversity or uniformity, and also the improvement of accessibility and environment neatness in the forest.